2020
DOI: 10.3390/cancers12123653
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-Derived GARP Induces Peripheral Regulatory T Cells—Potential Impact on T Cell Suppression in Patients with Melanoma-Associated Thrombocytosis

Abstract: Platelets have been recently described as an important component of the innate and adaptive immunity through their interaction with immune cells. However, information on the platelet–T cell interaction in immune-mediated diseases remains limited. Glycoprotein A repetitions predominant (GARP) expressed on platelets and on activated regulatory T cells (Treg) is involved in the regulation of peripheral immune responses by modulating the bioavailability of transforming growth factor β (TGF-β). Soluble GARP (sGARP)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(33 citation statements)
references
References 58 publications
5
28
0
Order By: Relevance
“…A number of studies have also reported on direct effects of platelets on T cell proliferation and cytokine production (29,51,58). Despite extensive washing, complex formation between platelets and DCs might occur during DC stimulation (13,41).…”
Section: Discussionmentioning
confidence: 99%
“…A number of studies have also reported on direct effects of platelets on T cell proliferation and cytokine production (29,51,58). Despite extensive washing, complex formation between platelets and DCs might occur during DC stimulation (13,41).…”
Section: Discussionmentioning
confidence: 99%
“…PLTs MPs cultured with Tregs prevented the differentiation into IL-17– and IFN-γ-producing cells in a P-selectin dependent manner ( 104 ). The co-cultures of CD4+ CD25- T cells with PLTs induced Tregs and this effect was abolished by the blocking of glycoprotein A repetitions predominant ( 105 ). In HIV, the aberrant function of CD8+ T lymphocytes was abolished when these cells were co-cultured with PLTs from HD, implying that direct contact with PLTs and TGF-β secretion contributed to this functional improvement ( 117 ).…”
Section: Platelets and Systemic Inflammationmentioning
confidence: 99%
“…Besides their essential role in hemostasis [52], platelets are involved in angiogenesis, wound healing and immunomodulation [53][54][55]. In cancer, they have been shown to promote tumor invasion [56][57][58][59] and cancer-associated thrombocytosis is an independent poor prognosis factor in multiple cancer types [60][61][62]. Tumors continually activate the coagulation pathways, which leads to thrombin formation and chronic platelet activation.…”
Section: Plateletsmentioning
confidence: 99%
“…Independent of their tumor stage, melanoma patients have shown a significant upregulation of GARP on the platelet surface, compared with healthy donors. Nevertheless, there was no difference in GARP expression between early- and late-stage melanoma patients [ 62 ]. GARP expression was also quantified by flow cytometry in Tregs from PB by Jin et al, but no difference was shown between subjects with lung cancer and healthy subjects [ 17 ].…”
Section: Garp As a Biomarker In Cancer: Perspectivesmentioning
confidence: 99%